Cross-cultural adaptation and validation of the Chinese version of the Spine Oncology Study Group Outcomes Questionnaire - Zhai, Shuheng; Xu, Nanfang; Liu, Shanshan; Liu, Zhongjun; Liu, Xiaoguang; Wei, Feng (Frontiers in Oncology, 2022)
Background Context Patients with spinal metastases always accompanied with poor health-related quality of life (HRQoL) with disease and treatment-related adverse outcomesThe Spine Oncology Study Group Outcomes Questionnaire (SOSGOQ) has been verified and validated in English for patients with spinal metastases, but not in Chinese. Purpose This paper aimed to complete the cross-cultural adaptation of the Chinese version of SOSGOQ and verify the reliability and validity, as well as to report the HRQoL of Chinese patients with spinal metastases. Study Design/Setting Single-center, prospective, observational cross-sectional study. Patient Sample 76 patients were enrolled in this study. Outcome Measures The SOSGOQ consists of 5 HRQoL domains (Physical Function, Neurological Function, Pain, Mental Health Social Function) and Post therapy questions. The Eq-5D 3L questionnaire covers 5 items in mobility, self-care, usual activities, pain discomfort, and anxiety-depression, with 3 answer options for every question. The SF-36 comprises of 36 items in 8 domains. Methods A single-center, prospective, observational cross-sectional study including patients with spinal metastases underwent surgery was conducted. HRQoL was evaluated using Chinese version of SOSGOQ, Medical Outcomes Study Questionnaire Short Form 36 Health Survey (SF-36) and EuroQol 5 Dimensions questionnaire (EQ-5D). Demographic, tumor, symptom, treatment data and Eastern Cooperative Oncology Group (ECOG) were collected. Reliability was evaluated by internal consistency reliability, convergent validity, concurrent validity and clinical validity. Spearman correlation analysis was used to analyze the relationship between variables. Results 76 patients were enrolled in this study with a mean age of 55.8 years. Kidney was the most common primary tumor site and thoracic spine was most affected. Internal consistency of the overall SOSQOQ (0.907) was higher than EQ-5D (0.819), and all items of SOSQOQ had a high convergent validity (>0.40). SOSGOQ was significant correlated with EQ-5D in respective domains (P<0.001) and overall score (P<0.001), while SF-36 was relate to the overall SOSGOQ score and most domains. Total SOSGOG was significant sensitive to change of ECOG (P=0.017), prior surgery (p=0.001), and tumor type (P=0.026). Conclusions The SOSGOQ is reliable and effective to evaluate HRQoL in patients with spinal metastases, with high sensitivity and specificity. Surgical treatment can significantly improve patients' HRQoL.